'Walling' Baghdad: Spatial dissonance and tactics of war. Issue 1 (1st March 2013) - Mehta, Brinda J.
This article examines the phenomenon of 'walling' in Baghdad. I demonstrate how barrier walls and internal borders represent a politicized manifestation of what Anibal Quijano calls the 'coloniality of power' (Quijano 2000: 533) a highly racialized and power-inflected Euro-centered discourse of Otherness destined to create distinctions between Euro-American 'civilization' and 'third world backwardness'. At the same time, I will also show how Iraqi writers and poets create resisting narratives that contest the walls of coloniality in an anti-occupation poetics. These writers also contest the sectarian and gender violence that results from physical and symbolic territorial demarcations destined to create a fragmented city and a violated national imaginary.